PELAKSANAAN, PEMBANGUNAN DAERAH PERBATASAN - Zaili Rusli, Ratty Puspitasari, Sujianto, (JIANA ( Jurnal Ilmu Administrasi Negara ), 2020)
Implementation, Development of Frontier Area.. The objectives of this research are to find out and analyze implementation of development in frontier area at Kabupaten Indragiri Hilir (Case Study in Kecamatan Kempas), impeller factor and resistor of development in spacially frointier area Kecamatan Kempas Kabupaten Indragiri Hilir. This research type is qualitatif descriptive approach. Research location in Kecamatan Kempas Kabupaten Indragiri Hilir. Technique in collection of sampel use sampling purposive technic. Data analysis use descriptive method of analysis. Technique analysis data is data collection, data reduction, data display, conclution drawing and verification. The result of research is implemention of development in spacially frointier area Kecamatan Kempas Kabupaten Indragiri Hilir have goodness. Planning process, implementation and observation of development executed better, but not yet maximally generalization of development. As for factor impeller implementation of development in frontier area is society participation and caring of society, while its resistor factor that is limitation of budget and conflict of authority.